2012
DOI: 10.1104/pp.112.197319
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Complex Subunit PFT1 Interferes with COP1 and HY5 in the Regulation of Arabidopsis Light Signaling      

Abstract: Arabidopsis (Arabidopsis thaliana) mutants hypersensitive to far-red light were isolated under a light program of alternating red and far-red light pulses and were named eid (for empfindlicher im dunkelroten Licht). The dominant eid3 mutant carries a missense mutation in a conserved domain of PHYTOCHROME AND FLOWERING TIME1 (PFT1), an important component of the plant mediator coactivator complex, which links promoter-bound transcriptional regulators to RNA polymerase II complexes. Epistatic analyses were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 86 publications
3
40
0
Order By: Relevance
“…Emerging evidence indicates that PFT1/MED25 plays multiple roles in a number of essential plant processes, including light signaling and flowering time (Cerdán and Chory, 2003;Wollenberg et al, 2008;Iñigo et al, 2012;Klose et al, 2012), JA-mediated pathogen defense (Kidd et al, 2009), organ growth (Xu and Li, 2011), abiotic stress (Elfving et al, 2011), and JA and abscisic acid signaling (Çevik et al, 2012;Chen et al, 2012). This is consistent with the expectation that individual Mediator subunits recognize and respond to a subset of the approximately 1,500 transcription factors present in the Arabidopsis genome.…”
Section: Pft1 Regulates Lateral Root and Root Hair Formation Throughsupporting
confidence: 70%
“…Emerging evidence indicates that PFT1/MED25 plays multiple roles in a number of essential plant processes, including light signaling and flowering time (Cerdán and Chory, 2003;Wollenberg et al, 2008;Iñigo et al, 2012;Klose et al, 2012), JA-mediated pathogen defense (Kidd et al, 2009), organ growth (Xu and Li, 2011), abiotic stress (Elfving et al, 2011), and JA and abscisic acid signaling (Çevik et al, 2012;Chen et al, 2012). This is consistent with the expectation that individual Mediator subunits recognize and respond to a subset of the approximately 1,500 transcription factors present in the Arabidopsis genome.…”
Section: Pft1 Regulates Lateral Root and Root Hair Formation Throughsupporting
confidence: 70%
“…MED25 interacts directly with the transcriptional activation domain of VP16 (Vojnic et al, 2011). The ortholog of MED25 in Arabidopsis, known as PFT1 (Phytochrome and Flowering Time1) (Cerdán and Chory, 2003;Bäckström et al, 2007), was identified as a factor involved in phy signaling and flowering time (Cerdán and Chory, 2003;Iñigo et al, 2012aIñigo et al, , 2012bKlose et al, 2012). Our future investigation will test the hypothesis that HMR's 9aaTAD interacts directly with PFT1 to promote gene activation.…”
Section: Hmr Is a Transcriptional Coactivator Required For The Expresmentioning
confidence: 91%
“…For instance, the Arabidopsis MEDIATOR SUBUNIT14 (MED14)/STRUWWELPETER is a key regulator of cell proliferation (Autran et al, 2002). MED25/ PHYTOCHROME AND FLOWERING TIME1 was first identified as a key regulator of flowering (Cerdán and Chory, 2003) and later found to regulate final organ size and light signaling (Xu and Li, 2011;Klose et al, 2012). MED18 was found to control flowering time and floral organ identity (Zheng et al, 2013).…”
mentioning
confidence: 99%